Bilateral Preiser Disease in a Patient with Sickle Cell Anemia - Catapano, Joseph; Overduin, Oluwatola O.; von Schroeder, Herbert P. (Journal of Hand and Microsurgery, 2020)
Preiser disease is a rare condition of avascular necrosis of the scaphoid occurring in the absence scaphoid fracture or trauma. While the etiology of Preiser disease remains unknown, it has been associated with steroid use, chemotherapy, and infrequently with systemic diseases. No reports have associated Preiser disease with hemoglobinopathy. Due to the rarity of Preiser disease, management remains controversial and evidence is limited. Here, we describe the case of a 32-year-old right-hand dominant male with sickle cell anemia and a 4-year history of bilateral wrist pain. Radiographs and gadolinium-enhanced magnetic resonance imaging revealed bilateral Preiser disease. He was successfully managed with a 1,2 intercompartmental supraretinicaular artery vascularized bone graft to the right scaphoid.
Keywords: Preiser disease; hemoglobinopathy; sickle cell disease; vascularized bone grafts